Biopolítica e ideología racista en Bolivia (2021)
The concept of biopolitics is undoubtedly situated in contemporary reflections with Michel Foucault as one of its notable representatives in theoretical development. In this sense, recent research, even stepping away from the ideas put forward by Foucault, has given way to valuable notions, as in the cases of Esposito, Agamben, and Lemke. Evidently, racism becomes important because of its magnitude and, above all, the actuality that crosses the limits in the complex Bolivian reality. The relationship between racism and biopolitics converges in a heated philosophical and political interpretation. In the reflections on racism in Bolivia, biopolitics can establish and connect aspects that have not been taken into account so far in what is called racist ideology.